Relation between apolipoprotein e gene polymorphism and lipid spectrum in hypertensive patients - Sai Krishna Ragh Varahabhatla; Buryak, V.; Буряк, Віктор Валерійович (My University, 2021)
Objective: To study the relationship between apolipoprotein E gene polymorphism and lipid spectrum modifi cation in hypertensive patients. Design and method: We examined 310 hypertensive patients (177 males and 133 females) ages 56,11±0,68 years and history duration 6,51±0,48 years, who were administrated with any antihypertensive components and no any specifi c lipid-lowering medications. According to offi ce blood pressure measurement the average brachial value was 141,33±1,34/87,62±0,79 mmHg. The lipid spectrum components and apolipoprotein E gene polymorphism were assessed using automatic clinical biochemical analyzer «Cobas c311» and amplifi er for single nucleotide polymorphism identifi cation «Thermal Cycler CFX96TM Real-Time PCR Detection Systems» accordingly. Statistical data were presented like mean ± standard error and 95% confi - dence interval. Statistically signifi cant difference was considered in case of P<0,05.
Keywords: тези доповідей